"Bai Lod" holistic health experienced by homebound older people in the southern Thai community. (20th January 2021) - Detthippornpong, Supussajee; Songwathana, Praneed; Bourbonnais, Anne
Abstract: Objectives: This qualitative descriptive study aims to explore the meanings of holistic health in the southern Thai culture experienced by homebound older people. Background: The ageing society necessitates many services to meet the holistic needs of older people. Homebound older people are commonly an understudied population who may view their holistic health and well‐being differently from others. Due to geographical differences and local Thai cultural context, exploring the holistic health in the southern Thai culture would help promote a healthy lifestyle and improve their health outcomes. Methods: Based on purposeful sampling, 16 key informants who were homebound older people (ages ≥ 60 years old) living at home in a rural southern Thai community were participated in semi‐structured interviews. Informants consisted of six males and ten females who were Buddhist and married. Their ages ranged from 79 to 99, including nine homebound older people who lived in a couple, and seven widows and widowers. Eight had completed the primary school, and others were uneducated. The data were analysed with a content analysis. Results: Most of the informants had chronic diseases. In a broad main theme, the informants described the holistic health in local context as 'Bai Lod; which means being alive with positive, active and independent functioning. This theme included three sub‐themes: self‐supporting or taking care of themselves, having the ability to control their health conditions and being proud as a healthy older adult. The older people described self‐supporting as the ability to perform their activities of daily living, take care of their own health and work independently (active living). Having the ability to control their health conditions meant functioning well physically, although being frail, by maintaining their health through self‐management, and having a good mental health during such a life‐changing situation. Older people valued the ability to live by themselves without being a burden to their family. They felt happy with their life. Conclusion: Holistic health was described as being positive and active at home, and influenced by beliefs and values related to good physical function, mental health and spiritual activities. These findings could help healthcare professionals better understand older people' health, well‐being and cultural care in order to develop alternative strategies to maintain, enhance and support an active life for homebound older people.